Impact of the Uganda Rwanda border conflict on the diplomatic relations in Uganda - Akullu Patience Doris (Uganda Christian University, 2024)
Intermittent tensions, trade disputes, and accusations of interference have characterized the conflict between the governments of Uganda and Rwanda. The influence this has had on Uganda's diplomatic relations has been immense. In regard to the stated above, the present dissertation explores a multimodal ramification for the cited conflict on trade, security cooperation, regional integration efforts, and Uganda's international image. Using a qualitative research method that involves in-depth interviews with government officials, diplomats, and experts, the study traces the causes of the conflict, the dynamics, and its implications for Uganda's foreign policy objectives. The examination will explain the complex interplay of domestic forces, regional politics, and international influences at play that dictates the trajectory of the Ugandan-Rwandan relationship. This dissertation discusses in detail the challenges and opportunities facing Uganda as it navigates the diplomatic complexities created for Uganda by the border conflict still ongoing. The study provided an all-rounded analysis of conflict implications on the Ugandan diplomatic landscape by understanding the historical context, events, and root causes of the conflict.